PRIMORDIAL INCEST, THE INTRUSION OF ISRAILIYAAT AND THE QUESTION OF EVOLUTION - Syeed, Sabreen Syeed (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2024)
The early Muslim attitude towards Israiliyaat was overwhelmingly negative because of the prohibitions on taking knowledge from the Judeo-Christian tradition. But over time a steady import of Israiliyaat literature made its way into Quranic exegesis. The Quran was revealed to correct and rectify the mistakes documented in the Bible (Q 16:64). The Quran was not revealed to be explained in the light of those fabrications. In this paper three important instances are discussed, and it is shown how the inclusion of Israiliyaat distorts the Quranic meaning and undermines the non-contradictory nature of the Quran. One of the cases i.e Adam’s children committing incest is analyzed in detail. While neither the Quran nor Hadith support this view, it is still used as the primary explanation for the progression of the human race. This paper discusses how the dismissal of this bizarre view is necessary as it goes against the Quran. But its dismissal brings in another significant question. If there were just two humans on earth, and incest is out of the question, then how did human lineage move forward? Thus, it becomes a necessity in such a scenario to assume that there were other humans along with Adam and Eve on earth. And this is Muslim Evolutionism as espoused by Iqbal, Abdus Sabbur Shahin, Adnan Ibrahim, Israr Ahmed and others. This view is proved to be more Quranic in spirit and is in line with rationality and demonstrable scientific evidence. This paper demonstrates how biblical fabrications in Tafsir literature obscure Quranic narratives and their elimination will bring about a better understanding of the Quranic view of the origin of life.